Small and Medium-Sized Enterprises under the Transformative Vision 2030 of Saudi Arabia - Kayani, Farrukh Nawaz; Alzaid, Osama Ibrahim (International Review of Management and Marketing, 2025)
Small and medium-sized enterprises (SMEs) play a very crucial role in driving economic growth, innovation, and job creation. Under Vision 2030, Saudi Arabia aims to position Riyadh as a strategic hub for SMEs, attracting both domestic and international entrepreneurs, investors, and the skilled labors. Riyadh’s geographic location also makes it accessible to the various regions within Saudi Arabia, creating a central node from which SMEs can reach wider markets both domestically and internationally. The Saudi government is investing in different infrastructure and urban development projects to support Riyadh as SMEs hub. For instance, the recently completed Riyadh Metro project worth 25 billion USD intends to foster a greater level of connectivity within the city and ease the access to essential services not only for the common masses but also for the businesses. Previously, SMEs in Saudi Arabia were confronted with the challenges, such as lack of access to financing, regulatory hurdles, and shortage of labor. Often, these barriers kept them from growing to the extent that they could potentially compete with the well-capitalized state enterprises and the multinational corporations. To address these challenges the Saudi Government introduced General Authority for SMEs “Monsha’at” with the aim of increasing SME’s contribution to the GDP by 35% by 2030. In this article we have thoroughly discussed the strategic importance of Riyadh as SMEs hub along with the different challenges that SMEs are facing. Finally, the article contributes on the possible policy routes for supporting and promoting the SMEs in Saudi Arabia.